1995
DOI: 10.1002/hep.1840210313
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone, insulinlike growth factor-1, and insulinlike growth factor binding proteins 1 and 3 in chronic liver disease

Abstract: The liver is the major source of circulating insulinlike growth factor-I (IGF-I) and has been suggested as a major source of at least two of the major binding proteins that modify its bioavailability. We aimed to assess the direct effects of liver dysfunction on serum levels of IGF-1 and its major binding proteins by measuring fasting levels of growth hormone, IGF-1, IGFBP-1, IGFBP-3, insulin, C peptide, and glucose in 35 patients with cirrhosis and during an oral glucose tolerance test in 16 of those patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
2
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 42 publications
8
76
2
1
Order By: Relevance
“…28,29 Nevertheless, to our knowledge, no published study has evaluated serum IGF-I levels in the osteoporosis associated with chronic liver disease. Like others, [30][31][32] we found low serum IGF-I levels, which were related to the severity of the liver disease. In our study, BMD in LS was positively correlated with serum IGF-I levels, and patients with osteoporosis had serum IGF-I concentrations lower than patients without osteoporosis.…”
Section: Discussionsupporting
confidence: 86%
“…28,29 Nevertheless, to our knowledge, no published study has evaluated serum IGF-I levels in the osteoporosis associated with chronic liver disease. Like others, [30][31][32] we found low serum IGF-I levels, which were related to the severity of the liver disease. In our study, BMD in LS was positively correlated with serum IGF-I levels, and patients with osteoporosis had serum IGF-I concentrations lower than patients without osteoporosis.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, patients with severe hepatic cirrhosis have demonstrated high fasting levels of IGFBP-1 that are accompanied by elevated insulin levels. Interestingly, these patients had a less pronounced insulin-mediated suppression of IGFBP-1 during an oral glucose tolerance test (35). A similar pattern has been described in patients with AMI and abnormal glucose tolerance among whom the suppression of IGFBP-1 was significantly decreased during an oral glucose tolerance test, a finding that has been interpreted as increased hepatic insulin resistance (20).…”
Section: Baseline Characteristicssupporting
confidence: 55%
“…GH could also regulate immunity and metabolism [6] . Furthermore, liver is the main target organ of GH in vivo, and the center of GH-IGF axis [7,8] . It has been found that decreased serum IGF-1, IGFBP3 and ALS had a close relation to liver reserve function and the prognoses of liver cirrhosis patients [9] .…”
Section: Discussionmentioning
confidence: 99%